Communication molecules (ncRNAs) mediate tumor-associated macrophage polarization and tumor progression - Yao, Min; Mao, Xuhua; Zhang, Zherui; Cui, Feilun; Shao, Shihe; Mao, Boneng (Frontiers in Cell and Developmental Biology, 2024)
Non-coding RNAs play important roles in tumor cells and macrophages and participate in their communication as messengers. Non-coding RNAs have an impact in tumor cell proliferation, migration, and apoptosis, and they also regulate the differentiation and regulation of immune cells. In macrophages, they stimulate the polarization of macrophages into M1 or M2 by regulating proteins related to signaling pathways; in tumor cells, non-coding RNAs can enter macrophages through exosomes and affect the latter polarization. The polarization of macrophages further regulates the biological functions of cancer cells. The direction of macrophage polarization determines tumor progression, angiogenesis and drug resistance. This often creates a feedback loop. Non-coding RNAs act as bridges between tumor cells and macrophages to regulate the balance of the tumor microenvironment. We reviewed the signaling pathways related to macrophage polarization and the regulatory mechanisms of non-coding RNA in tumor-associated macrophages M1 and M2, and discussed the potential applications and prospects of exosome engineering.